2023
DOI: 10.31004/jn.v7i1.7390
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Jarak, Durasi Dan Posisi Penggunaan Smartphone Dengan Kejadian Astenopia Pada Mahasiswa S1 Keperawatan Semester Viii Universitas Pahlawan Tuanku Tambusai

Abstract: Abstrak Penggunaan smartphone merupakan salah satu penyebab astenopia yang ditandai dengan ketegangan mata, rasa tidak nyaman, iritasi, sakit kepala dan rasa panas pada mata. Penggunaan smartphone yang tidak tepat seperti jarak yang dekat, durasi lama dan posisi yang salah dapat menyebabkan terjadinya astenopia. Tujuan penelitian adalah untuk mengetahui hubungan antara jarak, durasi dan posisi penggunaan smartphone dengan astenopia pada mahasiswa Program Studi S1 Keperawatan semester VIII Universitas Pah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Regarding the duration of social media use, a study conducted on 93 students found that 64.5% of students had social media usage duration of more than 5 hours per day and had a severe insomnia incidence of 35.5%. In addition, this study also conducted a bivariate analysis between the duration of social media use and the incidence of insomnia, it was found that there was a relationship between the two variables with a p-value of 0.002 (Fernando and Hidayat 2020). Similar results were also obtained in another study that cell phone use more than 5 hours per day was associated with shorter sleep duration and the incidence of insomnia (Tamura et al 2017).…”
supporting
confidence: 76%
“…Regarding the duration of social media use, a study conducted on 93 students found that 64.5% of students had social media usage duration of more than 5 hours per day and had a severe insomnia incidence of 35.5%. In addition, this study also conducted a bivariate analysis between the duration of social media use and the incidence of insomnia, it was found that there was a relationship between the two variables with a p-value of 0.002 (Fernando and Hidayat 2020). Similar results were also obtained in another study that cell phone use more than 5 hours per day was associated with shorter sleep duration and the incidence of insomnia (Tamura et al 2017).…”
supporting
confidence: 76%
“…Melatonin levels may not only play a role in the pathophysiology of vertigo, but may also predispose people to waking up from Rapid Eye Movement sleep with headaches. Overall, the above research and theories show a two-way relationship between sleep quality disorders and vertigo (Chattu et al, 2019;Harnod et al, 2015;Hidayat, 2020;Hirshkowitz et al, 2015;Holland et al, 2018).…”
Section: Quality Analysis Of Vestibular Vertigo Patientsmentioning
confidence: 80%
“…A person who has sleep quality problems will deal with a number of problems, including poor performance in college, irritation, psychological problems and health problems. Poor sleep quality can also cause time management irregularities, impaired concentration and decreased quality of life (Hidayat, 2020).…”
Section: Sleep Qualitymentioning
confidence: 99%
See 1 more Smart Citation